Analisis Reduksi Dimensi Produktivitas Jagung di Provinsi-Provinsi Indonesia Menggunakan PCA - Tarigan, Ester; Hutauruk, Hermina; Siahaan, Immanuel Son; Samosir, Enjelina (Interdisciplinary Explorations in Research Journal, 2024)
ABSTRACT This study aims to identify the main factors influencing variations in maize productivity across 38 provinces in Indonesia in 2023 using the Principal Component Analysis (PCA) method. Through the application of PCA, this study successfully simplified the data into a number of principal components that reflect most of the variability in maize productivity. The results revealed that productivity variations are mainly influenced by principal components representing important aspects such as cultivation techniques, climatic conditions, and land management. These components provide strategic insights for decision-makers and agricultural sector actors in designing more effective productivity improvement strategies, particularly in low-productivity areas. This research is expected to support efforts to increase maize yields in Indonesia as a whole, by deepening the understanding of the determinants of agricultural productivity. Keywords: PCA, Maize Productivity, Mathematical Reduction, Principal Components, Agricultural Technology ABSTRAK Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor utama yang memengaruhi variasi produktivitas jagung di 38 provinsi di Indonesia pada tahun 2023 dengan menggunakan metode Principal Component Analysis (PCA). Melalui penerapan PCA, penelitian ini berhasil menyederhanakan data menjadi sejumlah komponen utama yang mencerminkan sebagian besar variabilitas dalam produktivitas jagung. Hasil penelitian mengungkap bahwa variasi produktivitas terutama dipengaruhi oleh komponen utama yang mewakili aspek-aspek penting seperti teknik budidaya, kondisi iklim, dan pengelolaan lahan. Komponen-komponen ini memberikan wawasan strategis bagi pengambil keputusan dan pelaku sektor pertanian dalam merancang strategi peningkatan produktivitas yang lebih efektif, khususnya di wilayah dengan produktivitas rendah. Penelitian ini diharapkan dapat mendukung upaya peningkatan hasil panen jagung di Indonesia secara keseluruhan, dengan memperdalam pemahaman tentang faktor-faktor penentu produktivitas pertanian. Kata kunci: PCA, Produktivitas Jagung, Reduksi Matematika, Komponen Utama, Teknologi Pertanian